Rural Education and teacher professionalization challenges in Northwestern Rio de Janeiro State - Francisca Marli Rodrigues de Andrade; Marcela Pereira Mendes Rodrigues; Jacqueline de Souza Gomes (Universidade Federal do Norte do Tocantins, 2023)
The aim of the present article is to analyze Basic Education teachers' professionalization in three rural schools in Santo Antônio de Pádua County, -Rio de Janeiro State, Brazil. The adopted methodology followed the participatory observation, which allowed experiences lived in the investigated schools from 2015 to 2019 to raise data diversity. Most of all research results have shown abandonment by the public authorities regarding schools' infrastructure, teachers' initial and continuing training, as well as lack of both political-pedagogical projects and teaching/learning practices based on the principles set for Rural Education and the Pedagogy of Alternation. All these missing elements have impact on teaching autonomy and lead to the degradation in the identity and geography of communities that have attended and still attend to these schools.